Economic analysis of air-cooled chiller with advanced heat rejection. (January 2017) - Yu, F.W.; Ho, W.T.; Chan, K.T.; Sit, R.K.Y.; Yang, J.
Highlights: Random forest models for air-cooled chiller were developed. VSD, Mist and VSD + Mist modes were studied for heat rejection. Five top variables for model accuracy were identified. VSD mode gave the highest economic benefits. Abstract: This study analyses economic benefits of an air-cooled chiller retrofitted with advanced heat rejection features. The rated capacity was 282 kW and operating variables were monitored comprehensively to develop random forest models. The top five variables to ensure model accuracy were identified. Electricity savings were predicted by the models with 3 advanced operating modes: variable speed control for condenser fans with an adjustable condensing temperature (the VSD mode), mist precooling of condenser air (the Mist mode), and their composites (the VSD + Mist mode). The integrated part load value (IPLV) was 2.90, 3.31, 2.93 and 3.34 for the normal mode, VSD mode, Mist mode, and the VSD + Mist mode, respectively. For a chiller system serving an office building, the VSD mode gave the highest economic benefit with a simple payback of 10.83 yrs and an internal rate of return of 4.38% over a 15-yr life cycle.